Revision of the North American genus Scirites (Araneae, Linyphiidae) - Dupérré, Nadine; Paquin, Pierre (Zootaxa, 2007)
The genus Scirites Bishop & Crosby (1938) is revised and now includes Scirites pectinatus (Emerton 1911) the type species, and Scirites finitimus n.sp. Diagnoses, descriptions, locality records, habitat information and distribution maps are given for both species. A morphological analysis places the genus in the distal erigonine clade of Miller & Hormiga (2004) and sister to (Tapinocyba (Ceratinops + Parapelecopsis). Scirites pectinatus is a widespread species occurring mostly north of the 40th parallel; S. finitimus has been collected from sphagnum bogs mostly in the Great Lakes region with a single isolated collection in Washington state.